Dramatic recovery of vision in patient with acute central retinal artery occlusion treated with local intra-arterial tissue plasminogen activator. Issue 4 (15th April 2020) - Margolin, Edward A; Rai, Amrit; Goldfarb, Jeremy; Zaslavsky, Kirill; Kohly, Radha; Nicholson, Patrick
Abstract : Central retinal artery occlusion (CRAO) is a devastating disease resulting in severe visual loss in most cases. It has no proven treatment, and a variety of management options used clinically all have dismal rate of success. We report outcome of treatment with local intra-arterial thrombolysis administered 2.75 hours after devastating visual loss from incomplete CRAO.